Gums and stabilisers for the food industry 12 - Williams, Peter A.; Phillips, Glyn O. (Special publication (Royal Society of Chemistry (Great Britain)), 2004)
The latest volume in the successful Special Publication Series captures the most recent research findings in the field of food hydrocolloids. The impressive list of contributions from international experts includes topics such as:""Hydrocolloids as dietary fibre""The role of hydrocolloids in controlling the microstructure of foods""The characterisation of hydrocolloids""Rheological properties""The influence of hydrocolloids on emulsion stability""Low moisture systems""Applications of hydrocolloids in food products Gums and Stabilisers for the Food Industry 12, with its wide breadth of coverage.